Effect of self-esteem on the relationship between depression and bullying among teenagers in Malaysia - Uba, Ikechukwu; Yaacob, Siti Nor; Juhari, Rumaya; Abu Talib, Mansor (Canadian Center of Science and Education, 2010)
The study examined the moderating role of self-esteem in the relationship between depression and bullying among teenagers. The participants of the study were 242 teenagers aged 13 to 16 years, from selected secondary schools in Selangor, Malaysia. Self-esteem was measured with the Rosenberg Self-Esteem Scale, while teenage depression was measured with the Children Depression Inventory and bullying was measured using the Bully sub scale of the Peer Relationship Questionnaire. Findings of the study indicate no gender differences between males and females in self-esteem. The study further found a negative and medium correlation between depression and self- esteem, self-esteem and bullying and a positive and small correlation between depression and bullying. However, results of the study did not find self-esteem as a moderator. Recommendations of the study highlight the need to explore other variables such as religious and sports involvements as possible moderators in future studies.